Innovation of a Project Module Based on the Ajak Temani Mandiri Learning Model Integrated with Local Wisdom to Improve the Creative Dimension of Elementary School Students - Rukmi, Dian Aprelia; Nisa, Ana Fitrotun; Zulfiati, Heri Maria (Jurnal Prima Edukasia, 2025)
Creativity is one of the key dimensions in the independent curriculum. It is also a crucial skill to possess in the 21st century. This study aims to innovate a project module based on the Ajak Temani Mandiri learning model, integrated with local wisdom, to improve the creative dimension of elementary school students in a feasible and effective way. The study used Research and Development (R&D) with the Borg and Gall model, consisting of ten stages: (1) research and information collection, (2) planning, (3) developing a preliminary form of the product, (4) preliminary field testing, (5) product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. Data collection was done through interviews, observations, questionnaires, and documentation. Data analysis employed qualitative and quantitative descriptive techniques with inferential statistics. The subjects were 76 grade IV elementary school students. Results of the study showed: (1) a project module was developed, with characteristics in line with the ATM learning model. The module was integrated with local wisdom and incorporated Project-Based Learning (PBL), (2) the module was deemed "very feasible" for use based on product feasibility assessments. Validation scores from experts were as follows: material experts scored 97.00, elementary school learning resource experts scored 88.25, and practitioners scored 92.36, (3) the effectiveness test revealed that the developed module was effective in increasing students' creative dimensions. The pretest score was 35.03, categorized as "developing," and after using the module, the post-test score increased to 87.76, categorized as "already developing." This resulted in an N-Gain score of 0.81, indicating high effectiveness. In addition to enhancing creativity, the module also positively affected students' product scores. The pretest product score was 75.49, while the post-test score increased to 89.05. In conclusion, the project module based on the Ajak Temani Mandiri Learning Model, integrated with local wisdom, successfully improved the creative dimensions of elementary school students.